Introduction - Woźniakowska, Agnieszka; Łakowicz-Dopiera, Anna (Review of International American Studies, 2014)
For three summer days in August 2013 the International American Studies Association managed to attract scholars of all continents to travel to a Polish harbor town—Szczecin to contribute to the discussions on America(s) separated from other continents by two oceans. The title 'Oceans Apart' turned out to be an intellectual provocation which proved that the oceanic separateness was illusory as the discussions oscillated around the topics which were recognized and resonant in distant parts of the world. As the organizers intended, the speakers searched for new words to give meanings to old texts. The works of authors such as Herman Melville, Pearl Buck, Jack London, or Sir Arthur Conan Doyle inspired scholars to ask questions pertaining to the complexity of human nature and served as referential points in debates on other more modern texts. The old problems of exclusion, prejudice or stereotyping found new exemplification both in literature and in geopolitical observations. The oceanic metaphors and associations triggered a wide range of topics and multiple ways of interpreting them, thus proving that the oceans connect rather than divide people. The present issue addresses topics related to the notion of the ocean in two ways: those which concern issues outside of the world of literature and those which refer to specific literary texts. The first paper selected for this issue has been written by Regina Schober and is entitled ‘The World Wide Sea—Oceanic Metaphors, Concepts of Knowledge, and Transnational America in the Information Age’. Professor Schober received for this article the 2013 Emory Elliot Award, the award given to an outstanding paper submitted for an IASA conference. The second text, ‘History as an ocean’ written by Alicja Bemben, investigates the question of what history is and it discusses the relation between history and literature. It is followed by Jolanta Szymkowska’s text ‘From the American Wild West to Bojszowy: Józef Kłyk’s Westerns as Social Rituals’ in which the author examines the extent to which the American film genre influenced the western production of Silesian amateur director, and discusses the ritual purposes of Józef Kłyk’s productions. The three articles are followed by papers in which the ocean metaphor is directly related to literary texts. Thus Justyna Fruzińska discusses the process of maturation of young men in relation to three fictional characters: Jack London’s Humphrey Van Weyden in The Sea Wolf, Herman Melville’s Captain Amasa Delano from ‘Benito Cereno’ and eponymous Billy Budd, and their experiences on the sea. Pilar Martínez Benedí, in ‘Revolving the Vortex; or, Working through Trauma at Sea’ also addresses Hermann Melville’s work, Moby Dick, by attempting to examine relationship between a sea-vortex and the experience of working through trauma. Claudia Ioana Doroholschi’s text is a comparative study of Stephen Crane’s The Open Boat and S.T. Coleridge’s The Rime of the Ancient Mariner. Jacek Mydla’s ‘United by the Ocean? The Romantic Conan Doyle and the Transatlantic Sherlock Holmes’ focuses on how the metaphor of the ocean/water functions in Doyle’s story “The Five Orange Pips.” Valeria Gennero’s text ‘Pearl S. Buck and the Forgotten Holocaust of the Two-Ocean War’ discusses the notions of ‘national identity’ and ‘gendered violence’ in the context of Buck’s novel Dragon Seed. In the last article Hitomi Nabae examines the representation of Creole culture in Lafcadio Hearn’s writings. Anna Łakowicz-Dopiera and Agnieszka Woźniakowska